Small bowel obstruction caused by transmesosigmoid internal hernia - Ghaith, Ata M.; Al-Kharabsheh, Ahmad A.; Al-Sakarneh, Mohammad I.; Ghaith, Osama M. (International Surgery Journal, 2024)
Internal hernia is an uncommon occurrence contributing to intestinal obstruction, posing diagnostic challenges. Among the infrequent manifestations, one noteworthy type is associated with the sigmoid colon, categorized into three subtypes: inter-sigmoid, trans-mesosigmoid, and intra-mesosigmoid. We present a case of a 48-year-old female who presented with small bowel obstruction as an emergency. CT showed intestinal obstruction with translational point at mid jejunum without any mass identified. At laparotomy we identified an internal hernia in the sigmoid mesocolon with full thickness mesentery defect (transmesosigmoid), bowel was viable and reduced where the defected was closed. Early identification of internal hernia and early management prevent mortality and morbidity; sigmoid related hernia is rear type of internal hernia. Most internal hernia diagnosed during laparotomy searching for case of acute intestinal obstruction.